Apartment Housing in Canadian Cities, 1900–1940 - Dennis, Richard (Urban History Review / Revue d'histoire urbaine, 1998)
Apartment houses may be considered as a deviation from the North American ideal of single-family, owner-occupied homes. Unsurprisingly, therefore, they attracted substantial criticism when first erected in Canadian cities, especially in Toronto where anti-apartment bylaws were introduced in 1912. They were condemned as insanitary, anti-family, and a threat to established property values, undermining "cities of homes" both morally and economically. But they were also evidence of modernity and cosmopolitan sophistication, praised for their efficiency and appropriateness for new types of households leading new lifestyles. Hence their appearance in new cities in the Canadian West, especially in the 1910s, and their increasing popularity through the 1920s.Focusing primarily but not exclusively on Toronto, this paper discusses the history and geography of Canadian apartment housing during pre-World War I and inter-war building booms; the ways in which apartments were advertised and represented; and the diversity of building types, from luxury downtown apartment hotels to suburban walk-up efficiency apartments and even a few semi-philanthropic blocks. It concludes with some observations on the still under-researched questions of how apartment buildings were financed and who owned them.